HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG NUTRISI DENGAN KEJADIAN ANEMIA DALAM KEHAMILAN DI PUSKESMAS HUTAIMBARU KECAMATAN PADANGSIDIMPUAN HUTAIMBARU TAHUN 2016 - Pohan, Rostina Afrida; Khalida, Winny (Universitas Aufa Royhan, 2016)
One factor was the high incidence of anemia, the lack of knowledge of the signs, symptoms and the impact caused by anemia as a result if the individual is exposed to anemia She did not feel